Clusters as a Tool for Improving the Economic Efficiency of the National Economy - Askarovich, Ulashev Khubbim (European Journal of Life Safety and Stability (2660-9630), 2023)
This article examines the theoretical and practical essence of clusters, studies the problems of cluster development in agricultural production of the Republic of Uzbekistan, proposals for further improving the implementation of the cluster approach in the agro-industrial complex of Uzbekistan.